Habitual physical activities of selected LSU active and inactive students - San Diego, Chiedel Joan G. (La Sallian research forum, 2011)
Physical inactivity is the present major health problem. Living and practicing unhealthy lifestyle is the cause of inactivity. This work presents the comparison between the fitness level of active and inactive college students of La Salle University for the school year 2009-2010. In order to identify the students' level of physical activity, they were asked to answer the Baecke Questionnaire of Habitual Physical Activity. Weighted mean and percentage were used to present the description of the students' gender, age and their level of physical activity, The result of this study reveals that active students are doing high level of physical activity which may lead them to have a healthy and better life. Moreover, inactive students are practicing an unhealthy lifestyle like they often watch television during their leisure time instead of doing activities that would enhance their level of fitness. Since it is proven that inactive students are doing unhealthy lifestyle that may cause living a detrimental life, the PE department should create a Physical activity program that would motivate them do it whether it is done intrinsically or extrinsically. Active students are also very active in doing physical activities; it is also recommended that a maintaining, more shaping and toning program will be provided in order to maintain and enhance them more.